2016
DOI: 10.15408/akt.v7i3.2733
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Keadilan, Norma Ekspektasi, Sanksi Dan Religiusitas Terhadap Niat Dan Ketidak Patuhan Pajak

Abstract: Headline, the main news in the front of page of a newspaper, is a strategic place to convey information. Of course, headline in yellow journalism ought to be attractive with bombastic content's characteristic and sometimes it shows off sensuality. Koran Merapi is one of newspaper which has the positioning as a law and criminal newspaper. In other side, Criminal reality always shows some characters such as: suspect, police and victim. Based on constructivism ideas, mass media will always construct reality to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
1
4
0
7
Order By: Relevance
“…The results showed that the level of religious owned by men and women cannot be justified would be able to influence the perception of gender relations with the ethics of tax evasion, it takes other factors that could affect that relationship. The research result is consistent with the findings made by Basri & Surya (2014) that religiosity does not mediate gender relations with the ethics of tax evasion.…”
Section: Influence Of Gender On Ethical Perceptions Of Tax Evasion Wisupporting
confidence: 91%
See 1 more Smart Citation
“…The results showed that the level of religious owned by men and women cannot be justified would be able to influence the perception of gender relations with the ethics of tax evasion, it takes other factors that could affect that relationship. The research result is consistent with the findings made by Basri & Surya (2014) that religiosity does not mediate gender relations with the ethics of tax evasion.…”
Section: Influence Of Gender On Ethical Perceptions Of Tax Evasion Wisupporting
confidence: 91%
“…Such a condition can occur due to the men and women who work in accordance with the existing regulations would be directed him to behave ethically in accordance with the procedure when he was performing his duties so that this will encourage the achievement of ethical behavior regardless of the attitude of love of money. Basri & Surya (2014) that the love of money does not mediate gender relations with the ethics of tax evasion.…”
Section: Influence Of Gender On Ethical Perceptions Of Tax Evasion Mementioning
confidence: 97%
“…Other studies indicate that subjective norms have a powerful influence on non-compliance of taxpayer (Hite, 1997; Murphy, 2005; Jayanto, 2011; Wanarta and Mangoting, 2014). Perception of justice from the tax system and moral norms as well as previous research literature shows that there is a significant effect on the intention to behave non-compliant in taxation in Indonesia (Kelly, 1993;Damayanti, 2012;Basri and Surya, 2014).…”
Section: Introductionmentioning
confidence: 87%
“…Penelitian yang dilakukan (Mustikasari, 2007) (Feld & Frey, 2007). Minat merupakan tingkatan yang menyatakan seberapa jauh keinginan seseorang untuk berusaha keras dalam melakukan sebuah perilaku, atau usaha yang direncakanan individu untuk mengusahakan suatu perilaku tertentu (Ajzen, 1991 (Basri & Surya, 2014).…”
Section: Tabel 1 Jumlah Wajib Pajak Kabupaten Banyuwangiunclassified